Sleep quality among chronic kidney disease patients undergoing hemodialysis: a cross-sectional study - Setiawati, Estriana Murni; Kusumawati, Dewi Ayu (International Journal of Health Science and Technology, 2024)
Chronic kidney disease (CKD) is a terminal condition with high morbidity and mortality. Hemodialysis is one intervention of the end stage of CKD patients. It is impair sleep quality and affect on physical and mental health of the patient, which results in individual daily activities. The purpose of the study to determine the the sleep quality among CKD patients undergoing hemodialysis. This study used a cross-sectional design. The sampling technique used was purposive sampling. A total of 45 CKD patients undergoing hemodialysis participated in the study. Pittsburgh Sleep Quality Index (PSQI) questionnaire was used to measure the quality of sleep among CKD patients. Frequency distribution was used to analyze the result. The results of the study showed the quality of sleep among CKD patients undergoing hemodialysis was poor. Family and healthcare provider support and attention are needed to improve patient quality of sleep. Thus the patient can survive.